Consumer Preferences and its Importance in the Acquisition of Products in the 2021 Pandemic Period in Metropolitan Lima - Papanicolau Denegri, Jorge Nicolás A. (2023)
The results of the research on consumer preferences and its importance in the acquisition of products during the critical period of the pandemic in Metropolitan Lima from March to December 2020, when emotional and cognitive relationships increased when purchasing products, are shown in this article. This makes it possible to understand the extent to which, at that stage, consumers were willing to modify their purchasing habits, depending on their rationality or emotions, so as not to be affected by the crisis that was experienced at that time.